Effects of GhWUS from upland cotton (Gossypium hirsutum L.) on somatic embryogenesis and shoot regeneration. (May 2018) - Xiao, Yanqing; Chen, Yanli; Ding, Yanpeng; Wu, Jie; Wang, Peng; Yu, Ya; Wei, Xi; Wang, Ye; Zhang, Chaojun; Li, Fuguang; Ge, Xiaoyang
Highlights: GhWUS -overexpressing Arabidopsis induces somatic embryo and shoot formation from root tips. GhWUS overexpression promotes phytohormone-independent shoot and auxin-dependent embryo formation from excised Arabidopsis root. Overexpression of a GhWUS-SRDX chimeric repressor inhibits cotton embryogenic callus formation. Abstract: The WUSCHEL ( WUS ) gene encodes a plant-specific homeodomain-containing transcriptional regulator, which plays important roles during embryogenesis, as well as in the formation of shoot and flower meristems. Here, we isolated two homologues of Arabidopsis thaliana WUS ( AtWUS ), GhWUS1a_At and GhWUS1b_At, from upland cotton ( Gossypium hirsutum ). Domain analysis suggested that the two putative GhWUS proteins contained a highly conserved DNA-binding HOX domain and a WUS-box. Expression profile analysis showed that GhWUSs were predominantly expressed during the embryoid stage. Ectopic expression of GhWUSs in Arabidopsis could induce somatic embryo and shoot formation from seedling root tips. Furthermore, in the absence of exogenous hormone, overexpression of GhWUSs in Arabidopsis could promote shoot regeneration from excised roots, and in the presence of exogenous auxin, excised roots expressing GhWUS could be induced to produce somatic embryo. In addition, expression of the chimeric GhWUS repressor in cotton callus inhibited embryogenic callus formation. Our results show that GhWUS is an important regulator of somatic embryogenesis and shoot regeneration.